The clinical impact of rifampicin-based anti-TB therapy and tenofovir alafenamide-containing ARV regimen drug Interaction in people living with HIV: Case series report - Yahya Ali Mohzari; Mohammed AL Musawa; Ahmad Alrashed; Bandar Zaeri; Nader Damfu; Peter Cahusac; Sana Alwafai; Ahmad Alamer; Abdulaziz Almulhim (Elsevier, 2023)
Background: People living with HIV (PLWH) are prone to developing tuberculosis (TB). Since tenofovir alafenamide (TAF) is the recommended tenofovir (TFV) prodrug and rifampicin is a key component of TB therapy, thus complicating HIV and TB coinfection management. However, there is little data regarding the impact of this drug-drug Interaction in PLWH, which makes health care providers reluctant to prescribe them together. Methods: This was an observational, retrospective case series carried out at King Faisal Specialist Hospital & Research Center (KFSH&RC), Jeddah, Saudi Arabia. PLWH (≥18 years old) who received the TAF-containing ARV regimen and rifampicin-based anti-TB therapy together for ≥ 4 weeks were included. The objective of this study was to report the clinical impact of this drug-drug interaction (rifampicin + TAF-containing antiretroviral (ARV) regimen) on HIV viral load control in PLWH. Results: A total of 7 PLWH who met the inclusion criteria, 5 (71 %) out of 7, were males. All patients received dolutegravir 50 mg twice daily (DTG) plus the combination of TAF 25 mg and emtricitabine 200 mg (FTC) once daily as their ARV regimen. Four patients had suppressed viral load levels at baseline, which was maintained throughout TB treatment. Three patients had unsuppressed viral load levels at baseline and attained viral load suppression throughout the TB treatment course Conclusion: Overall, the TAF-containing ARV regimen maintained it's efficacy in presence of rifampicin.